Reconstruction of Chemical Castration Sanctions Implementation Based on the Medical Ethics Code (Comparison with Russia and South Korea) - Rian Saputra; M Zaid; Pujiyono Suwadi; Jaco Barkhuizen; Tiara Tiolince (Lex Scientia Law Review, 2023)
This study aims to reconstruct the ideal setting in the implementation of chemical castration sanctions in Indonesia based on the medical code of ethics. This research is a normative legal research, the approach used is a case approach, comparative approach and a conceptual approach, with a literature study research technique. The granting of the authority to execute chemical castration by a doctor is contrary to the principles contained in the medical code of ethics, including: First, it contradicts the principle of autonomy at the level of implementation of the principle of Autonomy which is applied in the form of the principle of "informed consent" where in carrying out his duties a doctor must first choose approval from the family and the patient for all actions that result in a decrease in the patient's physical endurance. Second, it is against the principle of non-maleficence, which prohibits actions that harm or worsen the patient's condition. Third, it is against the principle of beneficence. The rules regarding the implementation of chemical castration for perpetrators of sexual crimes against children can actually be followed by referring to the provisions for the implementation of chemical castration in Russia and South Korea, both countries whose medical profession will only serve as an advisory opinion for law enforcers who have been given special competency training.